A molecular study of pediatric pilomyxoid and pilocytic astrocytomas: Genome-wide copy number screening, retrospective analysis of clinicopathological features and long-term clinical outcome - AlShail, Essam; Alahmari, Ahmed Nasser; Dababo, Anas A. M.; Alsagob, Maysoon; Al-Hindi, Hindi; Khalil, Hala; Al Masseri, Zainab; AlSalamah, Razan; Almohseny, Ethar; Alduhaish, Amjad; Colak, Dilek; Kaya, Namik (Frontiers in Oncology, 2023)
Pilocytic Astrocytoma (PA) is the most common pediatric brain tumors. PAs are slow-growing tumors with high survival rates. However, a distinct subgroup of tumors defined as pilomyxoid astrocytoma (PMA) presents unique histological characteristics and have more aggressive clinical course. The studies on genetics of PMA are scarce. In this study, we report one of the largest cohort of pediatric patients with pilomyxoid (PMA) and pilocytic astrocytomas (PA) in Saudi population providing a comprehensive clinical picture, retrospective analysis with long-term follow-up, genome-wide copy number changes, and clinical outcome of these pediatric tumors. We examined and compared genome-wide copy number aberrations (CNAs) and the clinical outcome of the patients with PA and PMA. The median progression free survival for the whole cohort was 156 months and it was 111 months for the PMA, however, not statistically significantly different between the groups (log-rank test, P =0.726). We have identified 41 CNAs (34 gains and 7 losses) in all tested patients. Our study yielded the previously reported KIAA1549-BRAF Fusion gene in over 88% of the tested patients (89% and 80% in PMA and PA, respectively). Besides the fusion gene, twelve patients had additional genomic CNAs. Furthermore, pathway and gene network analyses of genes in the fusion region revealed alterations in retinoic acid mediated apoptosis and MAPK signaling pathways and key hub genes that may potentially be involved in tumor growth and progression, including BRAF, LUC7L2, MKRN1, RICTOR, TP53, HIPK2, HNF4A, POU5F, and SOX4. In conclusion, our study is the first report of a large cohort of patients with PMA and PA in the Saudi population that provides detailed clinical features, genomic copy number changes, and outcome of these pediatric tumors and may help better diagnosis and characterization of PMA.